Febrile Episodic Ataxia with Novel Mutation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
An episodic ataxia type 2 (EA2) kindred with ataxic spells induced by fever or high environmental temperature and a novel CACNA1A mutation were identified and reported from the Universities of Mississippi and Minnesota.